Prevalence of Pneumonia Associated with Measles among Infants and Children Hospitalized in Healthcare setups of Pakistan - Saleh Jan, Nusrat Ali, Ansar Hussain, Safia Bibi, Khalil Ahmad, Muhammad Rafiq Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pneumonia in children is the primary cause of morbidity in developing countries and one of the risk factor for Pneumonia is measles. Objective: The aim of this study was to find out the Prevalence of pneumonia associated with measles among infants and children hospitalized in Pakistan. Materials and method: The contemporary cross-sectional study was carried out at the pediatric department of Sifwat Ghayour Shaheed Memorial Hospital, Peshawar and HBS General Hospital, Islamabad from November 2022 to April, 2023, after taking the permission from the ethical boards of the institutes. A total of 154 individuals, infants and children of less than 5 years of both genders hospitalized and diagnosed with measles were enrolled in this study. After obtaining informed written consent, the patients' comprehensive demographic information was documented. Detailed demographic information about the patients, including height and weight, was recorded following the authorities' informed written consent. The prevalence of pneumonia and its symptoms in each patient were evaluated. The SPSS 22.0 version was used to analyze the data. Frequencies and percentages were used to evaluate categorical variables. Results: A total of 154 individuals were enrolled in this study out of which 62(40.2%) were infants and 92 (59.7%) were children. 32 (20.7%) individuals had a high socioeconomic position, 50 (32.4%) had an average socioeconomic status, and 72 (46.75%) had a poor socioeconomic status. 87 56.4% participants resided in a rural area. On the basis of severity 36 (23.3%) of the patients had mild measles, 46 (20.8%) had moderate measles, and 72 (46.7%) had severe measles. Pneumonia was found to be prevalent in 97 (65%) participants. 42 individuals (27.3%) had received a measles vaccine. Conclusion: In this study, we came to the conclusion that children with measles had a noticeably high rate of pneumonia(65%). Keywords: Children; Measle; Pneumonia.